1999
DOI: 10.4269/ajtmh.1999.61.760
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of host-related factors to low cure rates of praziquantel for the treatment of Schistosoma mansoni in Senegal.

Abstract: Abstract. Surprisingly low cure rates were repeatedly observed after treatment with a standard dosage of praziquantel in a recently established Schistosoma mansoni focus in northern Senegal. In 4 discrete cohorts from the same population, cure rates were 18-36% and egg count reduction rates were 77-88%. Data and material of 920 compliant subjects from all 4 cohorts were further analyzed to identify possible host-related factors associated with low cure rates. The lowest cure rates were found in the highest egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 21 publications
4
21
0
1
Order By: Relevance
“…(i) The low CR with PZQ at 40 mg/kg (18 to 36%) in the field were confirmed in four more study cohorts, consisting of various age and infection-intensity groups, in different seasons, with different timings of follow-up surveys, and with circulating antigen detection (72,130,137). (ii) CR remained abnormally low when the dose was increased to two consecutive doses of 30 mg/kg at a 16-h interval (73).…”
Section: Drug Resistance In Schistosomesmentioning
confidence: 88%
See 1 more Smart Citation
“…(i) The low CR with PZQ at 40 mg/kg (18 to 36%) in the field were confirmed in four more study cohorts, consisting of various age and infection-intensity groups, in different seasons, with different timings of follow-up surveys, and with circulating antigen detection (72,130,137). (ii) CR remained abnormally low when the dose was increased to two consecutive doses of 30 mg/kg at a 16-h interval (73).…”
Section: Drug Resistance In Schistosomesmentioning
confidence: 88%
“…(iii) CR with PZQ at 40 mg/kg rose to normal when the treatment was repeated after 2 to 4 months and were also normal in children originating from the area of endemic infection but living in an urban area with no transmission (108; A. Mbaye, D. Engels, L. Tchuente, and B. Gryseels, unpublished results). (iv) The efficacy of PZQ could be related to age and pretreatment intensity but not to other host factors, including behavioral and immunological parameters (137). (v) Application of a statistical model relating egg counts more accurately to worm numbers showed that the poor CR could be explained by the initial high intensity of infection, even if over 95% of the worms were killed (S. J. de Vlas, D. Engels, A. Mbaye, and B. Gryseels, Schistosomiasis Res.…”
Section: Drug Resistance In Schistosomesmentioning
confidence: 99%
“…In the mouse model, praziquantel efficacy depends on host antibody responses, and treatment increases the exposure of schistosome antigens at the worm surface (8,23,35). In humans, however, it proved difficult to identify the host-related factors that influence the efficacy of praziquantel (40,71). Pharmacokinetic studies found that orally administered praziquantel is rapidly and almost completely absorbed (maximum concentrations in serum are reached 1 to 2 h posttreatment) but undergoes extensive firstpass liver clearance and prompt metabolic processing into inactive metabolites.…”
Section: Antischistosomal Properties Of Praziquantelmentioning
confidence: 99%
“…1 A consistent finding for both is that 10-20% of those treated fail to clear their infection, although nearly 100% experience a reduction in the intensity of infection. 1,2 The factors associated with this fairly constant level of treatment "failure" have been primarily associated with very heavy infection and intense transmission, 3,4 as well as some level of noncompliance with taking these drugs. Because the drug does not affect immature stages of the parasite, drug efficacy may seem to be lower where many individuals have experienced a new infection within 4-6 weeks of treatment.…”
Section: Introductionmentioning
confidence: 99%